Reconstruction of Chemical Castration Sanctions Implementation Based on the Medical Ethics Code (Comparison with Russia and South Korea) - Rian Saputra; M Zaid; Pujiyono Suwadi; Jaco Barkhuizen; Tiara Tiolince (Universitas Negeri Semarang, 2023)
This study aims to reconstruct the ideal setting in the implementation of chemical castration sanctions in Indonesia based on the medical code of ethics. This research is a normative legal research, the approach used is a case approach, comparative approach and a conceptual approach, with a literature study research technique. The granting of the authority to execute chemical castration by a doctor is contrary to the principles contained in the medical code of ethics, including: First, it contradicts the principle of autonomy at the level of implementation of the principle of Autonomy which is applied in the form of the principle of